Fragile storytelling: Methodological considerations when conducting ethnographic fieldwork among people with Alzheimer's disease - Ida Marie Lind Glavind; Hanne Overgaard Mogensen (Elsevier, 2022)
The purpose of this article is to discuss the possibilities and challenges of qualitative research for studying the lifeworlds of people living with dementia. Historically, people with dementia have been widely neglected within qualitative research, being considered too incoherent or unintelligible. Though this has been contested, methodological challenges remain. Building on fieldwork among people with Alzheimer's disease in Denmark from 2019 to 2021, we argue that ethnographic methods have the potential to grasp the non-verbal presence and interaction crucial for describing "the moods" of social encounters and people's "signature". Yet, at the same time, the people who participated in the study were still trying to tell stories, highlighting the importance of also paying attention to their verbal expressions, however fragmented they may be. We use the term "fragile stories" and "fragile storytelling" referring to how people with Alzheimer's easily become distracted from the topic of conversation. Fragility implies the possibility of breaking, if not handled with care. Losing one's words risks derailing attempts to tell a story, and hence the sense of coherence and continuity, while also challenging the conversational partner's ability to properly relate to the story being told. Doing fieldwork among people with Alzheimer's highlights the fact that knowledge creation is an ongoing dialogic process, in daily life and in research. With inspiration from the concept of wayfinding (see Ingold 2000), we propose that the researcher must go along with the fragile stories by continually attuning to the person with Alzheimer's shifting modes of being. By doing so, the researcher can help the stories come into being by not just being present and listening with patience, but through guessing and filling in.